AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN KEUANGAN MASJID - Muhammad Mahardika; Adi Prasetyo; Firda Ayu Amalia (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This study aims to analyze the accountability and transparency of mosque financial management in the city of Malang, especially in mosques managed by the academic and non-academic community. The objects of this research are 4 Great Mosques in Malang City, namely AR Fachruddin Mosque, An-Nur Polytechnic Mosque, Abu Dzar Al Ghifari Mosque, and Sabilillah Mosque. This research uses descriptive qualitative method. Collecting data in this research is observation, interview and documentation. Sources of data in this study are primary data and secondary data. This research is motivated by mosques which usually only present financial reports which only include revenues that are generally obtained from the congregation and cash disbursements. The source of the mosque's funds cannot be clearly identified for what purpose the funds are used. The results showed that all mosques already had financial reports as a form of accountability. The mosque's financial manager has complied with the values of sharia accounting principles: accountability, justice and truth. These three principles are related to the characteristics possessed by the apostle: sidiq, amanah, tabligh and fathanah. Although, this study found that accounting practices are still not in accordance with accounting standards for non-profit entities. This is because the financial manager does not have a financial background. Most of the mosque's financial publications are announced just before Friday prayers and posted on the wall magazine.